PENGARUH STATUS SOSIAL EKONOMI ORANG TUA TERHADAP PRESTASI BELAJAR EKONOMI DAN PERILAKU KONSUMSI SISWA - Wirawan, Yahya Reka (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2015)
This study aimed to analyze the influence of socio-economic status of parents on the learning achievement of economic and consumption behaviors of students. The sample in this study were students majoring in sosial studies in high school Jombang City Year 2013/2014 as many as 155 people with a proportional random sampling technique. The data collection techniques used are questionnaire and documentation. The results showed that the socioeconomic status of the parents have a significant effect on economics learning achievement. Socio-economic status of parents significantly influence consumption behavior of students. So also with the economic study achievement significantly influence consumption behavior of students